ANALISIS PENGARUH PENGGUNAAN STRATEGI MARKETING MIX TERHADAP KEPUTUSAN PEMBELIAN PRODUK PADA MAPAN DIGITAL PRINTING LAMONGAN - M. Hafidh Nashrullah; Nawari Nawari (J-MACC, 2022)
This study uses a quantitative approach, nonprobability sampling technique in purposive sampling technique, and data collection techniques by means of library research, and questionnaires. The population in this study were all consumers who bought products at Mapan Digital Printing Lamongan, with a sample of 80 respondents. The data analysis technique uses multiple linear regression analysis. The results of this study are Simultaneous Test (f test) proving that the independent variable has a significant effect on the dependent variable with a value of 165,177 while the Partial Test (t test) shows that the place variable (X4) has a dominant influence on purchasing decisions with a value of 10,304. Determination coefficient value R2 obtained is 0.898 means that product, price, promotion, and place variables are able to explain purchasing decisions by 89,8% while the remaining 10,2% can be explained by other variables not examined in this study. Based on research on the influence of the marketing mix on the purchasing decisions of secondary food products at Mapan Digital Printing Lamongan, conclusions can be drawn as follows: (1) the results of the F test indicate that the marketing mix (product, price, promotion, and place) is jointly influential significant to the purchase decision of products at Mapan Digital Printing Lamongan. (2) From all marketing mix variables (products, prices, promotions, and places) obtained after testing t, it turns out that the place variable has the dominant influence in the purchasing decisions of secondary crops in Mapan Digital Printing Lamongan.